The Antimicrobial Effect of Cold Atmospheric Plasma against Dental Pathogens-A Systematic Review of In-Vitro Studies - Gert Jungbauer; Dominick Moser; Steffen Müller; Wolfgang Pfister; Anton Sculean; Sigrun Eick (MDPI AG, 2021)
Interest in the application of cold atmospheric plasma (CAP) in the medical field has been increasing. Indications in dentistry are surface modifications and antimicrobial interventions. The antimicrobial effect of CAP is mainly attributed to the generation of reactive oxygen and reactive nitrogen species. The aim of this article is to systematically review the available evidence from in-vitro studies on the antimicrobial effect of CAP on dental pathogens. A database search was performed (PubMed, Embase, Scopus). Data concerning the device parameters, experimental set-ups and microbial cultivation were extracted. The quality of the studies was evaluated using a newly designed assessment tool. 55 studies were included (quality score 31-92%). The reduction factors varied strongly among the publications although clusters could be identified between groups of set pathogen, working gases, and treatment time intervals. A time-dependent increase of the antimicrobial effect was observed throughout the studies. CAP may be a promising alternative for antimicrobial treatment in a clinically feasible application time. The introduced standardized protocol is able to compare the outcome and quality of in-vitro studies. Further studies, including multi-species biofilm models, are needed to specify the application parameters of CAP before CAP should be tested in randomized clinical trials.